Minimizing the time and cost of production of transgenic alfalfa libraries using the highly efficient completely sequenced vector pPZP200BAR - Jozefkowicz, Cintia (2016)
Alfalfa is the most important forage legume worldwide. However, similar to other minorforage crops, it is usually harvested along with weeds, which decrease its nutrient qualityand thus reduce its high value in the market. In addition, weeds reduce alfalfa yield byabout 50%. Although weeds are the limiting factor for alfalfa production, little progress hasbeen made in the incorporation of herbicide-tolerant traits into commercial alfalfa. This ispartially due to the high times and costs needed for the production of vast numbers oftransgenic alfalfa events as an empirical approach to bypass the random transgenicsilencing and for the identification of an event with optimal transgene expression. In thisfocus article, we report the complete sequence of pPZP200BAR and the extremely highefficiency of this binary vector in alfalfa transformation, opening the way for rapid andinexpensive production of transgenic events for alfalfa improvement public programs.